State of mood, motivation, and impulsivity of young athletes: a cross-sectional study - Karla Medeiros Costa; Claudio Andre Barbosa De Lira; Eduardo Macedo Penna; Marília Santos Andrade; Fabiano De Suza Fonseca; Dalton De Lima-Junior; Paulo Gentil; Alberto Souza Sá Filho; Gustavo De Conti Texiera Costa (Human Movement, 2022)
Purpose The aim of the study was to compare the mood, motivation, and impulsivity of young athletes of different sexes and ages.